11. CHARACTERISTICS AND RELATIONSHIP BETWEEN DENTAL ARCH SHAPE AND CLINICAL CROWN SURFACE OF UPPER JAW TEETH OF STUDENTS AT HANOI UNIVERSITY OF BUSINESS AND TECHNOLOGY (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the proportions and relationships between dental arch shapes and clinical crown surface shapes of the upper jaw teeth.Subjects and methods: Cross-sectional descriptive study from February 2024 to June 2024 on 86 students of the Faculty of Dentistry, Hanoi University of Business and Technology, aged 18 and over, at the Clinical Center, Faculty of Dentistry, Hanoi University of Business and Technology.Results: The proportions of the types of dental arch shapes in the upper jaw are: oval 79.07% (male 69.57%; female 90%); square 12.79% (male 19.56%; female 5%); triangular 1.16% (male 2.17%; female 0%); other shapes 6.98% (male 8.7%; female 5%). The proportions of the types of clinical crown surface shapes of the upper central incisors are: oval 60.47% (male 63.04%; female 57.5%); square 39.53% (male 36.96%; female 42.5%). The similarity ratio between the clinical crown surface shapes of the upper central incisors according to the shape of the upper dental arch is 53.49%, specifically: oval is 48.84%; square is 4.65%.Conclusion: In addition to the shape of the dental arch, prosthodontists should consider factors such as facial shape, gender, personality, age, shape, color and wear of adjacent teeth to choose the most suitable incisor shape for each patient.
Keywords: Dental arch shape; outer surface shape of tooth crown; central incisor.